Learning Video Media Using Dynamic Drawing Principles for Vocabulary Recognition to Improve Early Childhood Speaking Comprehension - Ni Luh Elin Widianingsing (Universitas Pendidikan Ganesha, 2023)
There are obstacles to low student learning outcomes. This is caused by teachers who only use the lecture method in the learning process, which results in students not playing an active role in the learning process. This research aims to create learning video media using the principle of dynamic drawing for vocabulary introduction to improve speaking comprehension for young children in group B kindergarten. The media development process follows ADDIE procedures. The data collection method uses a questionnaire, while the instrument uses a rating scale of 1-5. Data analysis was carried out using descriptive statistical methods and quantitative descriptive statistics to describe the average scores from experts regarding the learning video media being developed. The research results show that this learning video passed the validity and practicality tests well, with a